2013
DOI: 10.1097/aap.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Adductor Canal Block Versus Femoral Nerve Block for Analgesia After Total Knee Arthroplasty

Abstract: Adductor canal block preserved quadriceps muscle strength better than FNB, without a significant difference in postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
301
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(323 citation statements)
references
References 27 publications
13
301
0
9
Order By: Relevance
“…Mudumbai et al [25] compared a continuous ACB to a continuous FNB in patients undergoing TKA, but the primary outcome for this study was postoperative gait distance, which was found to be greater in patients who received an ACB. Similarly, Jaeger et al [26] performed a prospective study comparing continuous ACB to continuous FNB after TKA and found that patients in the ACB group had more preserved quadriceps strength. A more recent study by Kim et al [27] analyzed postoperative quadriceps strength and pain scores in patients who received either a single-shot FNB or ACB.…”
Section: Discussionmentioning
confidence: 95%
“…Mudumbai et al [25] compared a continuous ACB to a continuous FNB in patients undergoing TKA, but the primary outcome for this study was postoperative gait distance, which was found to be greater in patients who received an ACB. Similarly, Jaeger et al [26] performed a prospective study comparing continuous ACB to continuous FNB after TKA and found that patients in the ACB group had more preserved quadriceps strength. A more recent study by Kim et al [27] analyzed postoperative quadriceps strength and pain scores in patients who received either a single-shot FNB or ACB.…”
Section: Discussionmentioning
confidence: 95%
“…[9][10][11] To date, trials are lacking on the effect of a postoperative continuous saphenous nerve block after major ankle surgery.…”
mentioning
confidence: 99%
“…7 A continuous femoral nerve block can control pain from the saphenous territory, 8 but it leads to significant motor weakness of the quadriceps femoris muscle. 9 A supplemental continuous selective blockade of the sensory saphenous nerve might be suitable.…”
mentioning
confidence: 99%
“…Jaeger et al (14) reported no significant difference between the two groups regarding morphine consumption within 2, 4, 8 and 24 hours after surgery. In another study by Kim et al (15), no significant difference in supplemental analgesia was observed within 24 and 48 hours after general anaesthesia between the ACB and the FNB groups.…”
Section: Discussionmentioning
confidence: 99%